An Analysis of Sociomathematical Norms of Elementary School Students Through Collaborative Problem Solving Learning (Journal of Primary Education, 2019)
In Collaborative Problem Solving (CPS) learning, there is a problem-solving discussion which will bring to student interaction in solving the problems, these interactions are governed by a norm, the norm governing mathematics learning is the norm called as sociomathematics, in term of non ambiguity norm, third person comprehension, justification mathematical norm, differentiation mathematical norm, validation norm, relevance norm. This research has purpose to describe the application of sociomathematics norms in the learning of CPS. This research was a qualitative descriptive study by using subjects of elementary school students of SDN Jatingaleh 01. The total numbers of samples taken were 32 students who were divided into 13 male students and 19 female students. The data collection technique was by using observation, interview and documentation, whereas, the data analysis techniques was done by using triangulation technique. The results showed that the application of sociomathematics norms in SDN Jatingaleh 01 Semarang was quite well with the total percentage of 13% of students or 4 students considered in a good category, there are 59% or 19 students was in moderate category, and there was 28% or 9 students who considered in the less category in applying the sociomathematics norm. Meanwhile, the indicator of sociomathematics norm which is most widely adopted by students is Validation Norm where the majority of students agree that the solution chosen by the group to be applied in resolving a problem. Whereas, the norm which is less applied by the students in the mathematical problem solving process is Relevance Norm, this indicated that the fifth grade students have not been able to express or convey the suitability of the solutions offered by the existing problems.